Estrutura sociogenética de ninhos de Euglossini (Hymenoptera: Apidae) e estrutura genética das populações urbanas de Euglossa cordata do estado de São Paulo - Oi, Cíntia Akemi (2010)
Euglossine bees (Hymenoptera: Apidae) are important pollinators in the Neotropical region. These bees are widely studied by collecting males in attractive baits, but there are few reports from females. In this work, we studied Euglossini bees using molecular tools, collecting bees in nests and adults in flowers at different levels, individual, nest and population. In Chapter 1, we use a non-lethal strategy for obtaining DNA from antenna conducting mark-recapture experiments. We found by a chi-square test the same chance to recapture the two groups of bees (with intact antennae vs removal antennae); this result suggests that the removal did not affect the survivor of bees. The DNA extracted from the antennas was successfully used for microsatellite analysis. In Chapter 2, we determine the sociogenetic structure of nests using microsatellite loci. Genetic analysis of Euglossa cordata, Euglossa townsendi and Eufriesea violacea nests revealed that brood is usually explained by a single mating, which corroborates the literature. In chapter 3, we used mitochondrial genes to verify the genetic structure of populations of Eg. cordata. The sequencing of mitochondrial genes cyt b and COI by direct PCR product showed high variation in several positions, showing two peaks or the mismatch between forward and reverse sequence. This result suggests the occurrence of heteroplasmy, and then, we have cloned these products. The clones showed even greater intra-individual variation, suggesting the occurrence of associated numts and heteroplasmy. Due to this variation, we could not establish the genetic structure of urban populations in Eg. cordata, although there is some evidence of interpopulation differentiation for mitochondrial haplotypes. In conclusion, this work has made contributions to a better understanding of the biology of Euglossine bees; employing molecular tools, we bring new information about familial and population genetics of this group of bees.